Richard the third 1597 - Shakespeare, William (Oxford : Clarendon press, 1959)
The Old Vic Theatre, Old Vic Trust Ltd. in association with The Arts Council of Great Britain presents The Old Vic Company in the plays of Shakespeare, director Michael Benthall, administrative director Alfred Francis, "Richard II," by William Shakespeare, produced by Michael Benthall, decor and costumes by Leslie Hurry, music composed by Christopher Whelen..
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English drama; Theater programs -- England -- London; Theater programs -- 1955.